2005
DOI: 10.1007/s11062-005-0068-5
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia Induced by Microwave Irradiation of an Acupuncture Point under Conditions of Visceral Pain in Mice: Role of the Serotonergic Cerebral System

Abstract: We studied behavioral manifestations of analgesic effects induced in mice by irradiation of the E36 acupuncture point (AcP) by low-intensity microwaves under conditions of visceral pain evoked by i.p. injections of 0.08 ml of a 2% solution of acetic acid. We also examined changes in these analgesic effects resulting from a drop in the level of serotonin after i.p. injection of 300 mg/kg of a blocker of synthesis of serotonin, DL-parachlorophenylalanine (PChPhA). Two modes of irradiation were tested, with a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This effect is indicative of the development of rather intense analgesia after microwave irradiation of the antinociceptive AP; these findings agree well with the experimental data obtained by other researchers [18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This effect is indicative of the development of rather intense analgesia after microwave irradiation of the antinociceptive AP; these findings agree well with the experimental data obtained by other researchers [18].…”
Section: Discussionsupporting
confidence: 93%
“…In our previous studies [18,26] we demonstrated that the serotonergic system is significantly involved in the formation of the antinociceptive effect of microwaves. It was also shown that an additional mechanism of the action of analgin independent of inhibition of the activity of cyclooxygenase is related to activation of descending serotonergic pathways involved in the control of nociception [27].…”
Section: Discussionmentioning
confidence: 99%
“…This fact is, perhaps, related to summation of the actions of microwaves and tramadol on the central antinociceptive systems. It was found that the analgesic effect of microwave irradiation is mediated by serotonergic [9][10][11] and opioidergic [17,18] cerebral systems. Tramadol hydrochloride is a centrally acting analgesic with a complex mechanism of action: on the one hand, it is bound with μ-opioid receptors, while, on the other hand, it suppresses reuptake of noradrenalin by neuronal axon terminals and enhances the release of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained in experiments on animals [8][9][10][11], as well as results of treatment of patients with chronic pain syndromes [12,13], have demonstrated that there is an approach that provides weakening and, in some cases, even complete suppression of the pain syndromes; this is the action of low-intensity microwaves (with a nonthermal effect) on acupuncture points (APs). In our study, we examined the anesthetic effects of a synthetic opioid, tramadol, and microwave irradiation of an antinociceptive AP in mice.…”
Section: Introductionmentioning
confidence: 99%